The influence of information factors on professional success in coaching - Ivanovic, J. (Serbian Journal of Sports Sciences, 2009)
The aim of this work was to investigate the crucial factors which determine efficient functional informedness and professional success in coaching, as well as to describe coaches' information needs. The total sample included 63 coaches from 11 sport disciplines divided into the following groups of sports: power-speed sports (N=11), games (N=24), endurance sports (N=5), fighting sports (N=9), precision sports (N=14). The data were collected by an anonymous questionnaire with 46 questions. Based on a set model for gathering information and conditional factors on the one hand, and the data collected on information needs of coaches in Serbia on the other hand, we can conclude that the basic link of professional informedness based on the studied sample was undeveloped. In addition, some information factors have a great influence on the coach's professional success as regards the status of athletes he works with (coaching the junior or senior national teams). Coaches' professional success is conditioned by the internet use, the attendance at professional gatherings, reading primary static information sources, collecting technological information by reading professional journals, and publication of professional information gained through the work with athletes.